“Banuroja” (One Village with Three Religions): A Model of Social Harmony in Gorontalo - Ahmad Faisal (Institut Agama Islam Negeri Madura, 2019)
Banuroja is an acronym for “Bali, Nusa Tenggara, Gorontalo and Java”. From its naming identity, it appears that the community is heterogeneous both in terms of ethnicity, language, culture and religion. The heterogeneity of the people of Banuroja Village is actually an element that strengthens the harmony between them. There does not appear to be arrogance from followers of a particular religion, there is no excessive militancy, there is no intrigue to negate each other. This study shows that there are five aspects which are the key words of the Banuroja social harmony, namely (1) aspects of education and youth; (2) aspects of settlement and tradition; (3) aspects of work; (4) aspects of village government institutions; and (5) other aspects such as the prominent figures / religious elites. The driving aspects of integration on the one hand are actually at the same time a trigger for conflict on the other side. The author argues that the people of Banuroja have succeeded in showing that harmony is not just passive co-existence, not an artificial harmony. Living in diversity, in the context of Banuroja, actually being actualized by active co-existence in intimate friendship dissolves in the specialness of each rite without denouncing the other rites.